1925 N.C. Sess. Laws 530 - (:unkn) unknown (My University, 1925)
Pub.-Local Laws, ch. 460, § 4: It shall be unlawful to trap for bear or to run or hunt deer with dogs or to use while hunting any gun having a "Maxim silencer" or any other device thereon that will muffle the report of such gun, nor shall any gun be used that does not produce when discharged the usual and ordinary report.
Keywords: HUNTING REGULATION; SUPPRESSORS